Online teaching notes - Zeki, Akram M.; Saleh, Nor Hatini; Senan, Shayma (IIUM Press, 2011)
This system is intended to develop a learning management system. The system provides the learning documents or files in forms of lecture notes and slides for the students in IIUM for both Kuantan and Gombak campuses. The system will store all documents as mentioned for a specific course taken and for all faculties (kulliyyah) that are offered by IIUM. By using the system, the students are able to have access to other faculties' resources. Furthermore the system may be accessible by the students at any time so it's a gateway for the students to achieve excellence in their learning process.